DEVELOPING LEARNING MEDIA IN THE FORM OF “VAM” BASED ON VIDEO SCRIBE TO MEASURE THE LEVEL OF STUDENT LEARNING MOTIVATION IN CIVIC EDUCATION - Dyan Hari wobowo; Mochamad Yusuf Zen (JOSAR (Journal of Students Academic Research), 2022)
The background of this research is the results of the 1st Semester Final Exam in PPKn Subject are the lowest results. The reason, low of interest in PPKn subjects. Limited resources and too much material, while teachers have not used multimedia-based media as a learning support media, whereas schools have LCD Projector facilities that can be used for the learning process.This study aims to develop learning media, determine the feasibility of the media, and find out the differences in learning outcomes before and after using multimedia-based learning media using the Aplikasi Sparkol video Scribe on the material Harmonisasi Hak dan Kewajiban Asasi Manusia in the Pancasila Perspective of PPKn subjects in class XI of SMA 1 Kademangan.This type of research is Research and Development (R and D) with the development method. Determination of the feasibility level of multimedia-based learning media based on expert validation tests and small-scale trials was then applied to the sample class. The technique of collecting data using a questionnaire. Based on the results of the study it can be concluded that the implementation of the learning process can improve student learning outcomes, by looking at the results of the average value and completeness of learning of students.